Patrimônio regional: a criação de uma cartilha para valorização da gastronomia de São João do Polêsine – RS - Grellmann, Janaina Rubia (2022)
The cuisine of a certain place is fundamental for the cultural identity of the society. In this way, teaching about culture should not be limited to history, but contemplate heritage, tangible and intangible, to preserve the origin, and can be applied in an interdisciplinary way. Thus, the present work starts from the idea of the preliminary project inserted in the Geopark, which includes the area of Quarta Colônia, in the central region of the state of Rio Grande do Sul. Inserted in the teaching profession, the author of the present study came to understand many movements, opening several questions about this place, inserted in the field of investigation. Considering the importance of preserving the local cuisine, it is necessary to preserve it with the heritage, supporting the objects used for teaching the culture of the region, including gastronomy. Thus, the objective of the present study is to analyze the gastronomy of the Quarta Colônia region and understand how it can be worked in kindergarten schools, in the municipality of São João do Polêsine, through studies related to the objects. This is exploratory qualitative research, where bibliographical research and interviews will be used to substantiate and elaborate a booklet for the preservation of gastronomy in early childhood education. The results indicate that the cuisine promoted by Italian immigrants has undergone several adaptations, however, they do not erase the identity of the cuisine, with the appreciation of cultural roots. It is concluded that gastronomy must be preserved from material and immaterial heritage, and that the booklet is a type of didactic support that, dedicated to children's education, collaborates with students' learning about their cultural roots, promoting cultural appreciation.